1999
DOI: 10.1007/s100510050743
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and static light scattering study of the formation of cross-linked PMMA gels

Abstract: Free radical co-polymerization of methyl methacrylate (MMA) and ethyl glycol dimethyl metacrylate (EGDMA) was investigated in solution at different molar ratios R = [EGDMA]/[MMA] between 0 and 0.05. Initially mainly linear PMMA was formed with weight average molar mass 7.5×10 4 g/mol independent of R. At larger reaction extents branched polymers were formed and the systems gelled. The scattering intensity rose initially with the reaction extent, but reached a plateau value at larger reaction extents. The plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 16 publications
5
27
0
Order By: Relevance
“…DLS experiments show a remarkably similar behavior of g 2 (t) for very different gel-forming systems such as silica (8,9), Laponite (10), polyurethane (11), polysaccharides (12), PMMA (13), and globular proteins (14). Usually, a fast decay is observed followed by a stretched exponential decay sometimes preceded by power law decay.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…DLS experiments show a remarkably similar behavior of g 2 (t) for very different gel-forming systems such as silica (8,9), Laponite (10), polyurethane (11), polysaccharides (12), PMMA (13), and globular proteins (14). Usually, a fast decay is observed followed by a stretched exponential decay sometimes preceded by power law decay.…”
Section: Introductionmentioning
confidence: 69%
“…The moment when this occurs is highly system-dependent as is the fraction of trapped concentration fluctuations. DLS measurements of both cross-linking silica spheres (8) and flexible PMMA chains (13) showed that the relaxation of concentration fluctuations close to the gel point could be well described in terms of this model.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…An interesting parallel with chemical gels can be drawn. In the latter case, slow modes due to structural inhomogeneities have a q-dependence of their relaxation times which is described by high exponents (s s V qd with d = 3-4) [57] but in this case the diffusion of inhomogeneities on large length scales is inhibited by the presence of permanent crosslinks. Both for ionomers and covalent gels, the slow mode is due to relaxation of the structural inhomogeneities which take place by different mechanisms.…”
Section: Qualitative Descriptionmentioning
confidence: 99%
“…In all cases the correlation functions were characterized by a narrow relaxation time distribution. We calculated the apparent diffusion coefficient from the relaxation rate as D a = /q 2 and found that data at different concentrations superimpose if D a /D c is plotted as a function of q · ξ , see The correlation functions of the protein gels are typical for a wide range of gelling systems (21)(22)(23)(24)(25)(26)(27). Before the gel point the concentration fluctuations relax via cooperative diffusion and internal motion.…”
Section: Resultsmentioning
confidence: 99%